Pengaruh Gaya Hidup, Motivasi Belajar dan Kesempatan terhadap Kecurangan Akademik dengan Religiusitas sebagai Variabel Moderasi (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis UNISMA dan UMM Tahun 2020) - Utami, Putrilia Dwi Shintya Adi; Diana, Nur; Hidayati, Irma (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research was conducted at the Faculty of Economics and Business, Islamic University of Malang and Muhammadiyah University of Malang. The method used in this research is purposive sampling, the aim of this research is to determine the influence of Lifestyle, Learning Motivation and Opportunities on Academic Cheating with Religiosity as a moderating variable. The independent variables used are Lifestyle, Learning Motivation and Opportunity, the moderating variable is Religiosity and the dependent variable is Academic Cheating. The sample used in research was 94 respondent who were students from the Faculty of Economics and Business at UNISMA and UMM in 2020. The data collection technique used a questionnaire. The analytical methods used are instrument tests, normality tests, classical assumption tests and hypothesis tests using SPSS computer software for data processing. The result of this study show that Lifestyle has a positive effect on Academic Cheating, Learning Motivation has a negative effect on Academic Cheating, Opportunity has a positive effect on Academic Cheating, Religiosity has a negative effect on Academic Cheating, Religiosity is able to moderate the effect of Lifestyle on Academic Cheating, Religiosity cannot moderate the effect Learning Motivation on Academic Cheating, Religiosity is able to moderate the influence of Opportunity on Academic Cheating.Keywords : Lifestyle, learning motivation, opportunity, religiosity, academic cheating